Menyongsong Masyarakat Sadar Hukum: Peran Pendidikan Kewarganegaraan dan Kerjasama Dalam Penegakan Keadilan - Emellya Fridamayanti; Muhammad Iqbal Muzakki; Putri Octa Ivani; Wahjoe Pangestoeti (Pusat Riset dan Inovasi Nasional, 2024)
Citizenship education is very important to instill legal awareness, principles of justice, and an understanding of human rights. This education provides a deep understanding of the constitution, judicial system, human rights, and various other laws. This not only increases public awareness of the importance of obeying the law, but also instills good ethics and morals in individuals through values such as honesty, justice and social responsibility. In addition, the values of Pancasila serve as the main foundation in shaping the character of citizens. good country. It is hoped that the next generation will become citizens who are aware of their rights and obligations as members of society and are able to defend the values of Pancasila. The state and society are responsible for fighting crime, including unsolved murder cases. It is very important for law enforcement agencies and the community to work together to ensure that the legal process is fair and transparent and provides appropriate protection to victims and their families. Through active community participation in providing information and support to law enforcement agencies, criminal cases can be uncovered and resolved appropriately, resulting in a safer and fairer environment for everyone.